Effects of respiratory sarcopenia on the postoperative course in elderly lung cancer patient: a retrospective study - Dong Jae Han; Kwon Joong Na; Taeyoung Yun; Ji Hyeon Park; Bubse Na; Samina Park; Hyun Joo Lee; In Kyu Park; Chang Hyun Kang; Young Tae Kim (Journal of Cardiothoracic Surgery)
Abstract Objectives Recently, sarcopenia has been linked to unfavorable outcomes in various surgical procedures, including lung cancer surgery. This study aimed to investigate the impact of respiratory sarcopenia (RS) on postoperative and long-term outcomes in elderly patients undergoing lung cancer surgery. Methods This retrospective study included patients aged 70 years and older who underwent lobectomy with curative intent for lung cancer between 2017 and 2019. RS was defined as having values below the median for both the L3 skeletal muscle index, measured from preoperative PET-CT images, and peak expiratory flow (PEF). An inverse probability of treatment weighting (IPTW) approach was applied to balance covariates between the RS and non-RS groups. Baseline characteristics and postoperative outcomes were compared between groups using t-tests and chi-square tests. Kaplan–Meier curves and log-rank tests were used to compare overall and recurrence-free survival. Multivariable logistic regression analysis incorporating IPTW weights was performed to assess the impact of RS on respiratory complications. Results A total of 509 patients were included, of whom 123 (24.2%) had RS. After IPTW adjustment, baseline characteristics, including pulmonary function, were similar between the RS and non-RS groups. All patients underwent lobectomy, with 78.8% of the RS group and 80.9% of the non-RS group undergoing minimally invasive surgery. The RS group had a significantly higher rate of respiratory complications compared to the non-RS group (14.5% vs. 7.7%, p = 0.041). Multivariable logistic regression analysis showed that male sex (odds ratio = 15.2, p < 0.01) and lower DLCO (odds ratio = 0.96, p < 0.01) were significantly associated with respiratory complications, whereas RS did not show a significant association (p = 0.05). No significant differences were found in overall survival (p = 0.11) or recurrence-free survival (p = 0.51) between the groups. Conclusions In this study, RS had a limited impact on both postoperative and long-term outcomes in elderly patients undergoing lung cancer surgery. These findings suggest that other factors, such as DLCO and male sex, may play a more prominent role in predicting respiratory complications.